Analisis Implementasi Kebijakan Peraturan Gubernur Provinsi Dki Jakarta Nomor 90 Tahun 2018 Tentang Peningkatan Kualitas Permukiman Dalam Rangka Penataan Kawasan Permukiman Terpadu Di Kampung Kwitang Jakarta Pusat - Ramadhan Maksum Prayitno; Samsudin Samsudin (Jurnal Ilmu Administrasi Publik, 2022)
The author of this study presents the topic titled Analysis on Implementation of Governor of Special Capital Region of Jakarta Province Regulation Number 90 Tahun 2018 on Improvement of Quality Settlement in Integrated Settlement Management in Kampung Kwitang Central Jakarta by viewing the phenomenon particularly the accidental fire which burned down 31 houses of the residents situated at Jl. Kembang V Kwitang Village Senen Sub-District Central Jakarta Administrative City On 13 March 2021 and affected 67 household heads and 201 lives, the author is concerned with discovering the implementation, constraints and solutions to rebuild the burned-down settlement area. To study this, the author employed the theory of policy implementation according to Edward III. This method used in this study is descriptive with qualitative approach. The result of the research suggests that the Governor Regulation Number 90 of 2018 in Kampung Kwitang has been properly implemented and the objection by several local residents to 30-cm backward movement of house borderline for public road expansion was amicably resolved with a solution acceptable to all relevant parties